¿Mundos casi paralelos?: Las similitudes de una Marca de Alta Moda y una Multinacional de Productos de Conveniencia - Gallardo Landauro, Claudia (2019)
In times as variable as the century we live in, adapting to the needs of the environment is essential to survive market competition; However, the real challenge lies in identifying the future needs of the consumer and being able to develop products or services that satisfy them. This challenge arises in many of the existing industries, so we can say that both Procter Gamble and Louis Vuitton must deal with it. This text explains how the giants of innovation teach the industry of trends, fashion shows and fabrics how to obtain administrative success in such a changing market.